Новые данные о роли LRR-рецепторной киназы Sym19 в формировании бобово-ризобиального симбиоза и арбускулярной микоризы у гороха - Штарк, О.Ю.; Овчинникова, Е.С.; Лимпенс, Э.; Жуков, В.А.; Борисов, А.Ю.; Федорова, Е.Е.; Бисселинг, Т.; Тихонович, И.А. (Фактори експериментальної еволюції організмів, 2013)
Aims. This study was aimed to identify a role of regulatory symbiotic gene presented by a pea (Pisum sativum L.) mutant allele sym41 in nodule and arbuscular mycorrhiza (AM) development. Methods. Light microscopy, synteny-based mapping, RT-PCR, and complementation analyses were used. Results. AM fungal colonization was shown to be impaired at the epidermis whereas arbuscule formation in the cortex was not affected. Rhizobial infection and symbiosome formation were most strongly affected in apical nodule meristem-derived cells. The gene Sym41 was revealed to encode the common symbiotic LRR-receptor kinase SYM19. The mutation in sym41 causes a strong reduction (~90 %) of wild-type transcript levels in the mutant. Conclusions. A novel essential role for SYM19 in symbiosome differentiation was revealed. A higher demand for SYM19 levels was suggested for microbial infection of cells of apical meristem/epidermis than of primordium/cortex.